2021
DOI: 10.1089/neu.2021.0074
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diffusion Tensor and Kurtosis Imaging and Outcome following Mild Traumatic Brain Injury

Abstract: In this prospective cohort study, we investigated associations between acute diffusion tensor and kurtosis imaging (DTI; DKI) metrics and persistent postconcussion symptoms (PPCS) 3 months after mild traumatic brain injury (MTBI). Adult patients with MTBI (n=176) and community controls (n=78) underwent 3 Tesla MRI within 72 hours postinjury, estimation of cognitive reserve at 2 weeks, and PPCS assessment at 3 months. Eight DTI and DKI metrics were examined with Tract-Based Spatial Statistics. Analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The result of increased FA, MD, and rather an unchanged RD was supported by Veeramuthu et al ( 46 ) indicate that the supporting cells like astrocytes migrate to the site of injury, and caused the increase of cells density and diffusivity. Fourth, decreased MK was reported in a few studies on mTBI patients, and it was probably associated with degenerative changes and neuronal shrinkage ( 12 , 14 , 20 , 54 57 ). Furthermore, decreased ODI indicated that WM fibers tended to be parallel, which is consistent with the FA results in our study.…”
Section: Discussionmentioning
confidence: 95%
“…The result of increased FA, MD, and rather an unchanged RD was supported by Veeramuthu et al ( 46 ) indicate that the supporting cells like astrocytes migrate to the site of injury, and caused the increase of cells density and diffusivity. Fourth, decreased MK was reported in a few studies on mTBI patients, and it was probably associated with degenerative changes and neuronal shrinkage ( 12 , 14 , 20 , 54 57 ). Furthermore, decreased ODI indicated that WM fibers tended to be parallel, which is consistent with the FA results in our study.…”
Section: Discussionmentioning
confidence: 95%
“…After mild TBI, a part of patients experienced persistent post-concussion symptoms (PPCS) for several months to years ( Polinder et al, 2018 ). Compared to the patients who recovered and healthy controls, mild TBI patients who developed PPCS showed more severely damaged white matter microstructural integrity after brain injury ( Stenberg et al, 2021 ). In severe TBI, high FA at the initial scan could predict favorable GOS outcome of 1 year, and increased FA in the internal capsule and in centrum semiovale during follow-up of 1 year, particularly in patients with favorable GOS outcome ( Sidaros et al, 2008 ).…”
Section: Advanced Magnetic Resonance Imaging Based Techniquesmentioning
confidence: 99%
“…In the chronic phase after mTBI, most reports believe that FA values are reduced (Palacios et al, 2020;Oehr et al, 2021;Stenberg et al, 2021).…”
Section: Diffusion Magnetic Resonance Imagingmentioning
confidence: 99%